PENGARUH PERILAKU KEPEMIMPINAN TRANSFORMASIONAL TERHADAP PENILAIAN KINERJA DITINJAU DARI PERSPEKTIF LEARNING AND GROWTH DALAM BALANCED SCORECARD DI RUMAH SAKIT UMUM DAERAH KARANGANYAR - Maya Widyana Dewi (Jurnal Akuntansi dan Pajak, 2015)
Maya Widyana Dewi, 2014. The Influence of Transformational Leadership To Valuation Observed From Learning And Growth Perspective of Balance Scorecard In Rumah Sakit Umum Daerah Karanganyar. The research was carried in order to know the influence behavior of transformational leadership that consist of Idealized Influence, Inspirational Motivation, Intellectual Stimulation and Individualized Consideration, in a partial (dimentional) or simultant (all of it) to valuation measurement that is observed from learning and growth perspective of balanced scorecard in RSUD Karanganyar. This research was carried out using survey method, is a research that takes a sample from a population and using questioner as an instrument with judgmental sampling. The sample is 112 fixed employee in RSUD Karanganyar, medic and non medic employee. While the result of the analysis shows, in a partial manner, transformational leadership that has the shape of inspirational motivation and individualized consideration have significant influence to valuation observed from learning and growth perspective, whereas idealized influence and intellectual stimulation have not. A simultant manner, idealized influence, inspirational motivation, intellectual stimulation and individualized consideration have powerful influence to valuation observed from learning and growth perspective in Balanced Scorecard.Key word : balanced scorecard, kepemimpinan, kinerja, learning and growth